Innovative retrofit of unreinforced CHB wall-type houses - Tadili, Nikkei Pfeiffer M.
The Philippines is frequently affected by high-damage events like storms and earthquake, as such, structures must be designed to withstand these events to avoid failure that may consequently compromise occupants' safety. Although there are codes that account for these safety considerations, poor workmanship and budget constraints usually result into structures that become unsafe in the event of either an earthquake or a storm. Therefore to improve on a structure's safety and reliability during high damage events, retrofitting must be done. A typical Filipino home which is built out of concrete hollow block walls will be studied for retrofitting. The most appropriate retrofit which is the installation of surface treatment retrofits was implemented using chicken wire mesh and bamboo strips. The performance of walls with the hybrid grid was compared to the performance of the unreinforced wall. Through experimentation by seeing which wall could withstand the largest impact load, it was found out that the proposed scheme performed better than the unreinforced walls. The proposed retrofitting scheme was able to surpass the performance of the unreinforced wall by almost 10 times. Aside from this, the proposed scheme was also cost effective and the installation of the retrofit was very intuitive.